PEMBERIAN AROMATERAPI LEMON UNTUK MENURUNKAN NYERI AKUT PADA PASIEN FRAKTUR DI IGD - Ahmad Muzaki (Jurnal Ilmiah Keperawatan, 2023)
Background: A Manus fracture is a broken bone in the fingers caused by direct and indirect blows from the location of the hand to the fingers. Acute pain is a sensory or emotional event associated with actual or functional tissue damage, with onset sooner or later and of mild to severe intensity occurring for less than 3 months. Aromatherapy is a non-pharmacological treatment in the form of liquids made from plant extracts known as aromatic compounds. Objective: This study aims to obtain a description or real experience in providing nursing care to clients of extra manus fractures by administering lemon aromatherapy. Research Methods: This study used a case study design that included interviews, physical, examinations and documentary research. From the data analysis, the main nursing problem emerged, namely acute pain. One of the 1x8 hour nursing actions for clients with acute pain in manus extra fracture is giving lemon aromatherapy. Results: The results of the research conducted showed that both clients experienced a decrease in pain intensity on a scale of 7 to 6. Conclusion: Problems in both clients can be overcome by marked pain cucumber clients it is hoped that from the results of this study, if there are clients who experience manual fractures, they can be given lemon aromatherapy to reduce pain.